Caribbean Report 28-01-1997 - Orr, Carol (anchor); Ninvalle, Pete (correspondent); Lewis, Vaughn (interviewee); Vitalis, David (interviewee); Maharaj, Ramesh (interviewee); McDonald, Ronald (interviewee); Fraser, Tony (correspondent); McDonald, Ronald (interviewee); Grant, Jennifer (correspondent); Patterson, P. J. (interviewee); Allen, Gary (interviewee); Tripathi, Ramjit (interviewee); et al. (The British Broadcasting Corporation, 1997)
In this report St. Lucia’s Prime Minister, Dr. Vaughn Lewis has indicated a willingness to talk with St. Lucia Media Workers Association in an attempt to end the impasse over what the association sees as disparaging remarks made about them. Next, Trinidad and Tobago’s Attorney General is urging his Caricom colleagues to enter into agreement with external states to save the region from the evil of narcotics. Following, Britain’s desire to stop the drug trade coming out of the Caribbean is once again highlighted. Next, Jamaica and Haiti are said to enter into a framework corporation agreement. Jamaica’s Prime Minister is due to visit the Republic during the weekend. The aim of the visit is to form a joint commission to promote technical and economic corporation. In the following segment, Trinidad and Tobago’s Prime Minister, Basdeo Panday raps up a four day visit to India. He pledges to maintain business links and contacts with the land of his forefathers. Concluding the report, Australia defeats the West Indies and retain the Sir Frank Worrell trophy.
1. Headlines (00:00-00:31)
2. St. Lucia's Prime Minister, Vaughn Lewis says he is willing to talk with the St. Lucia Media Workers Association in an attempt to end their news blackout. Vaughn Lewis, Prime Minster of St. Lucia and David Vitalis, President of St. Lucia's Media Workers Association are interviewed. Pete Ninvalle report from Castries, St. Lucia (00:32-03:06)
3. Attorney Generals gather in Port of Spain over agreements with external states in a bid to fight drug traffickers. Ramesh Maharaj, Attorney General of Trinidad and Tobago is interviewed. Tony Fraser reports from Trinidad (03:07-04:58)
4. The Caribbean drug trade. Ronald McDonald, Investigator, is interviewed (04:59-08:44)
Keywords: Media Workers Association -- St. Lucia.; Media workers -- St. Lucia.; Attorney General -- Trinidad and Tobago.; Narcotics -- Caribbean Area.; Caribbean Community.; Drug trafficking -- Caribbean Area.; Framework corporation -- Haiti.; Framework corporation -- Jamaica.; Panday, Basdeo.; Visits of State -- India.; Cricket -- West Indies.